Efficacy of dupilumab in the treatment of severe vulvar pruritus associated with lichen sclerosus et atrophicus: a case report - Du, Na; Mao, Qiuyu; Yang, Jingyi; Zhang, Yiwen; Lyu, Xinyan; Li, Yueyue; Min, Wei; Xu, Jing (Frontiers in Medicine, 2024)
Lichen sclerosus et atrophicus (LSA) is a chronic inflammatory skin lesion with an undefined cause, which is believed to be related to autoimmune, genetic factors, infections and other factors. It primarily affects the skin and mucous membranes, and is more commonly found in the genital area, particularly in adolescents, premenopausal women and postmenopausal women,with a higher prevalence in females than males[1,2]. Recent relevant research findings suggest that Th1 cells play a role in the cascade of related inflammatory cytokines (interferon-γ, CXCL9, CXCL10, CCR5, CCL4, CCL5), however, the itching of LSA is difficult to be explained by the cascade of these cytokines[3].The primary treatment for LSA involves the administration of potent topical corticosteroids, with a gradual tapering of the dosage once symptoms have subsided. Additionally, topical calcineurin inhibitors are utilized to mitigate the risk of cutaneous atrophy associated with prolonged use of topical corticosteroids.LSA is difficult to treat and often recurs. Dupilumab is increasingly being used for the treatment of itching in non-atopic dermatitis patients by inhibiting the IL-4/IL-13 signal transduction, but there are few reports on its use for the treatment of LSA.Here, we present a case of LSA in a 61-year-old woman with extensive vulvar itching. Given the known itch-relieving effects of dupilumab[4], we explored its therapeutic potential in this refractory LSA case.